Clinical Profile of a Cohort of Heart Failure Patients in Girardot, Colombia (2024)
ABSTRACT: Introduction: Heart failure (HF) stands as the leading cause of hospitalization within cardiovascular diseases and represents a substantial economic burden on the healthcare system. In Colombia, its prevalence is high and escalating. Further information is needed to characterize the signs and symptoms of HF patients, particularly those with preserved and intermediate left ventricular ejection fraction (LVEF). This study aims to delineate the clinical and paraclinical profile of HF patients in an intermediate city of Colombia. Methods: Observational cross-sectional study using data from medical records of HF patients treated between July 2018 and December 2019 at a hospital in Girardot, Colombia. Results: 208 patients met inclusion criteria, with 63% being male. The median age ranged from 70 to 79 years. Among them, 82% exhibited preserved or intermediate LVEF. The most common etiology was arterial hypertension (76%), and the most frequently prescribed medications were beta-blockers. Conclusions: This study discusses the clinical and paraclinical profile in the context of global literature and, predominantly, Latin American literature. It highlights key aspects for the prevention and enhancement of clinical and preventive management of HF, with particular emphasis on the phenotype of preserved and intermediate LVEF.